Analysis of Overcurrent Protection on Nuri Feeder of Yarmokh PLTD Due to Short Circuit - Ekawati Margaretha Ohee; Yakobus Yakobus; Oktavianus Kati; Dultudes Mangopo (G-Tech: Jurnal Teknologi Terapan, 2025)
Protection systems are security mechanisms designed to safeguard electrical equipment from technical malfunctions, natural disturbances, operational errors, and other causes. These systems serve as electrical safety measures in power systems installed in power distribution networks, power transformers, electric power transmission lines, and generators, all of which protect the electrical system from faults or overloads. This research aimed to determine the short-circuit current and the overcurrent relay settings for the Nuri feeder at PLTD Yarmork. The method employed in this study involved collecting primary data directly from the field through observation and load measurements on transformers and distribution network lengths, followed by manual calculations. The research findings indicated that the maximum short-circuit current resulting from a three-phase fault at a fault location of 0% along the feeder was 6978.448 A, while the minimum current at 100% was 2313.838 A. For two-phase faults, the maximum short-circuit current at 0% feeder length was 976043.513 A, and the minimum current at 100% feeder length was 2003.842 A. The calculated TMS settings were 0.147 for the outgoing side of the OCR and 0.270 for the incoming side. Overall, the computed settings for both the overcurrent and earth fault relays were aligned with the field settings.